Development history, bottleneck and suggestions of evaluation system on centers for disease prevention and control in China - Na ZHANG; Ayan MAO; Danlei WANG; Wuqi QIU (Editorial Office of Chinese Journal of Public Health, 2023)
The establishment of the National Administration of Disease Prevention and Control marks the beginning of the reform of disease prevention and control system in China. With the transformation of the functions of centers for disease prevention and control (CDCs), the evaluation system on CDCs' performance should also be adjusted accordingly. In this paper, we systematically summarize the development process of the evaluation system on CDCs' performance in China; we also analyze current problems for the evaluation system in detail, including untimely update of evaluation policy documents, lack of theoretical basis for the establishment of evaluation indicators, coexistence of multiple problems in evaluation methods, insufficiency of horizontal comparability and vertical dynamics of the evaluation indexes. At last, we put forward suggestions for improving the evaluation system.